Deployment of Location Mapping Results Based on Application Programming Interface - Primaadi Airlangga; Abdul Arif Rachman (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
All user mapping data that has been created in the gis web can also be displayed on the user's own web and can also be displayed through mobile gis. By applying for tokens first to the admin for validation so that the mapping data can be displayed through API-based tokens. When the user wants to display in his own web then the user must enter the mapbox token first and if the user does not have a mapbox token then the user is directed to create a mapbox token first. first into the mapbox whose link has been provided, the purpose of inputting mapbox tokens is to display html scripts / code that are just copy paste in hopes of making it easier for users to see the mapping that has been made.in the gis web to his personal web without creating any more scripts and can be run And for mobile we just copy paste the tokens that are already in the gis web then The mapping data can be displayed immediately.oute of the trip.